2004
DOI: 10.1097/00005537-200406000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Modified Translabyrinthine Approach and Hearing Preservation

Abstract: In our patients, Class 1 or 2 hearing was preserved in 50% of the patients, with no persistence or tumoral relapse. The follow-up has obviously been short, but the first results are encouraging and deserve to be studied further in a more comprehensive survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…HL has been described in radiologically static tumors as well as in large ANs 1 . Hearing preservation is possible after surgery for selected ANs, but the results are quite variable, 12,13 and it appears to be more successful in small ANs (<2 cm) than in large tumors 14 . Despite this, delayed HL may occur irrespective of tumor recurrence 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HL has been described in radiologically static tumors as well as in large ANs 1 . Hearing preservation is possible after surgery for selected ANs, but the results are quite variable, 12,13 and it appears to be more successful in small ANs (<2 cm) than in large tumors 14 . Despite this, delayed HL may occur irrespective of tumor recurrence 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Mohr et al 12 described both incomplete filling of the internal auditory canal on preoperative magnetic resonance imaging and a tumor size of 15 mm or less as favorable factors for hearing preservation surgery when using a retrosigmoid surgical approach. The translabyrinthine approach has been modified, resulting in an approach that yielded preservation of hearing in 6 of 12 patients 13 . These efforts will hopefully result in a greater percentage of patients who will benefit from conservation of hearing after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that seem to be most important for hearing preservation are preservation of the cochlear nerve, CPA vasculature, maintenance of a fluid-filled vestibule, and preservation of endolymphatic fluids. 4 7 17 Smith et al suggested that the collapse of the saccule and/or the ductus reuniens may have preserved the cochlear fluids. 5 Rizvi et al suggested that in their patient, while attempting to seal off the middle ear with bone wax, they may have sealed off the ductus reuniens, which contributed to the stability of the hearing in their patient.…”
Section: Discussionmentioning
confidence: 99%
“…The modified translabyrinthine approach has been widely described elsewhere 19 . In brief, a total mastoidectomy is performed and the semicircular canals are resected (taking care to avoid damage to the membranous labyrinth) and sealed with bone wax.…”
Section: Methodsmentioning
confidence: 99%
“…introduced another modified translabyrinthine approach and reported encouraging hearing outcomes. They emphasised the need to completely close off access to the vestibule of the semicircular canals in order to preserve hearing function 19 …”
Section: Introductionmentioning
confidence: 99%